Risk assessment of heavy metals contamination in sediment and aquatic animals in downstream waters affected by historical gold extraction in Northeast China. Issue 3 (2nd April 2016) - Zhu, Hui; Xu, Yingying; Yan, Baixing; Guan, Jiunian; Zhou, Qingwei; Liang, Yinxiu
ABSTRACT: To assess the risk of heavy metals contamination on the aquatic ecosystem in downstream waters of a gold field in Northeast China, samples of sediment, fish, shrimp, and mussels were collected to determine heavy metals concentrations. According to Igeo, more attention should be given to Hg, Pb, and Cu pollution in sediment of Weisha River. For aquatic animals, the greatest contents of Hg, Cu, and Pb were found in samples collected from Weisha River, while the maximum values of Zn, Cd, and Cr were found in Hongshi Reservoir, Banmiao River, and Songhua Lake, respectively. The Hg and Pb contents in fish were found in the order of predatory fish > omnivorous fish > herbivorous fish, although for other metals no significant difference was observed among the three trophic levels. The contents of metals in Oriental river prawn and Chinese pond mussel were greater than that in fish, except for Pb. The Target Hazard Quotient and Hazard Index of metals showed that the Carnivorous and Omnivorous fish from Songhua Lake and Hongshi Reservoir, as well as all fish from Banmiao River and Weisha River, were not suitable for consuming in the view of the combined risk of all metals.